2005
DOI: 10.1002/pros.20312
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical expression of tumor antigens MAGE‐A1, MAGE‐A3/4, and NY‐ESO‐1 in cancerous and benign prostatic tissue

Abstract: Our data underline the peculiar relevance of cancer testis antigens expression in prostate cancers, with potential implications regarding both diagnosis and therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 18 publications
2
24
0
Order By: Relevance
“…An alternative possibility is that the MAGE-A6 peptides evaluated bare sufficient sequence or conformational homologies to proteins present in the environment to which many individuals may have become naturally primed against, allowing for functional cross-reactivity to be detected in our assays. This type of phenomenon has been previously suggested for the HLA-A2 -presented MART-1 [27][28][29][30][31][32][33][34][35] + Tcell responses against MAGE-A6 peptides predicted to be promiscuously presented by HLA-DR alleles and naturally processed rMAGE epitopes. CD4 + Tcells were isolated from the indicated (A) 14 melanoma patients and (B) 7 normal donors and tested for their ability to be stimulated by, and react against, the indicated MAGE-A6 peptides.…”
Section: Cd4mentioning
confidence: 59%
See 1 more Smart Citation
“…An alternative possibility is that the MAGE-A6 peptides evaluated bare sufficient sequence or conformational homologies to proteins present in the environment to which many individuals may have become naturally primed against, allowing for functional cross-reactivity to be detected in our assays. This type of phenomenon has been previously suggested for the HLA-A2 -presented MART-1 [27][28][29][30][31][32][33][34][35] + Tcell responses against MAGE-A6 peptides predicted to be promiscuously presented by HLA-DR alleles and naturally processed rMAGE epitopes. CD4 + Tcells were isolated from the indicated (A) 14 melanoma patients and (B) 7 normal donors and tested for their ability to be stimulated by, and react against, the indicated MAGE-A6 peptides.…”
Section: Cd4mentioning
confidence: 59%
“…Diseases such as viral myocarditis, lyme disease, rheumatoid arthritis (45), multiple sclerosis (46), and virus-induced autoimmune diabetes (47,48) have long been considered to be initiated or exacerbated by microbial pathogens. As was previously noted for the HLA-A2 -presented, melanomaassociated MART-1 [27][28][29][30][31][32][33][34][35] epitope (35), we hypothesized that the high degree of normal donor response against the MAGE-A6 Th peptides might be due to the cross-reactivity of T cells initially primed in vivo against highly homologous peptides within environmentally encountered proteins. After performing a homology search of the GenBank database, we selected the MPHF2 216-229 and CHP [42][43][44][45][46][47][48][49][50][51][52][53][54][55] peptides as two likely candidate homologues of the MAGE-A6 172-187 and MAGE-A6 280-302 peptides, respectively.…”
Section: Discussionmentioning
confidence: 88%
“…In urothelial TCC, a clear association between mRNA expression and grade was reported, with a progressive increase in frequency from 0% in grade 1 tumours to 44% in grade 4 tumours. 42 This contrasts with prostate cancer where no clear relationship was seen between IHC detection of NY-ESO-1 and LAGE-1, prostate specific antigen (PSA) or Gleason score, 29 although further evaluation in prostate cancer is warranted because patient selection in this study excluded those with a Gleason score of 8 or higher and expression has previously been shown to be more prevalent in metastatic prostate cancer. 41 In ovarian cancer, higher frequencies of NY-ESO-1 expression were found in serous carcinomas, whereas tumours of borderline malignancy or cystadenomas were negative.…”
Section: Factors Affecting Ny-eso-1 Expression In Tumoursmentioning
confidence: 87%
“…27 The majority of formalin-fixed tumour specimens display a heterogeneous cytoplasmic pattern of staining of NY-ESO-1 Ag. 4,28,29 It is not known whether heterogenous expression is a stable trait or varies over time (i.e., those cells that fail to stain at one time may nonetheless express Ag at some other time point). This will have implications for the interpretation of IHC results and hence patient eligibility for vaccination.…”
mentioning
confidence: 99%
“…34 Further, NY-ESO-1 expression was also found in biopsies from 3% of localized prostate cancer and 15% of hormone refractory prostate cancer patients by immunohistochemistry. 35 Lethe et al 36 reported that expression of MAGE-A1 was observed in 10.8% of carcinoma samples, whereas multi-MAGE-A and NY-ESO-1/LAGE-1 stained 85.9% and 84.8% of samples using immunohistochemistry, suggesting that a panel of CTAs rather than individual ones maybe more valuable as biomarkers. Recently, Smith et al 37 showed that SSX protein expression was restricted mainly to metastatic prostate cancer and not expressed in any primary prostate cancer using immunohistochemistry.…”
Section: Ctas As Potential Biomarkers In Prostate Cancermentioning
confidence: 99%